Wheat cultivars adaptation in Rio Grande do Sul. II. Adequacy of early cultivars to the July sowing - Osório, Eduardo Allgayer; Moreira, João Carlos Soares; Silva, Enedino Corrêa da (Pesquisa Agropecuaria Brasileira, 2014)
The performance of 15 cultivars of wheat planted in July was analyzed from data collected in 70 wheat field trials. These 70 trials, conducted in 1968, 1969 and 1970, were located in 16 places of the state, Rio Grande do Sul, and included six wheat producing regions. Except in region II, all the cultivars yielded better when sowed in June than in July. In each region, the cultivars that yielded better in June were also the best cultivars in July and in general they were the best cultivars in all the state. The farmers who need to plant wheat late (in July) would be advised to select from among the following cultivars which were tested: IAS 55, Lagoa Vermelha, IAS 52, IAS 54, IAS 51-Albatroz, IAS 56 and IAS 53.